Seroprevalensi Bovine Cysticercosis pada Sapi Bali di Nusa Tenggara Barat, Indonesia (SEROPREVALENCE OF BOVINE CYSTICERCOSIS AT BALI CATTLE IN WEST NUSA TENGGARA, INDONESIA) - Dharmawan, Nyoman Sadra; Damriyasa, I Made; Mahardika, I Gede (Jurnal Veteriner, 2018)
Bovine cysticercosis is one of the animal and public health problems throughout the world. Besides this disease has a negative impact on public health, also causing economic losses for farmers due to heavy infected carcasses should be rejected. Until now the availability of data related to this parasitic disease, especially in the Nusa Tenggara region is very limited.The purpose of this study was to obtain information on the prevalence and distribution of bovine cysticercosis on bali cattle in West Nusa Tenggara, Indonesia. The study was conducted by examining of bali cattle sera obtained from the farmer by ELISA (Bio-X Diagnostics’s Cysticercosis Antigen ELISA Kit). The results of ELISA examination of 92 serum samples with cut off 0.295, shows that there are 4 positive sera (4.35%). Three positive sera are originated from Lombok and one positive sera from Sumbawa. These results indicate that Lombok Island and Sumbawa Island in West Nusa Tenggara are not free from bovine cysticercosis. Since C. bovis infection is zoonotic, studies of risk factors are necessary, as well as the availability of information about the estimated burden of disease and the economic loss of the disease. It is recommended that veterinarians be more accurate when conducting post mortum examination, especially on the cattle which comes from a positive area.